Accelerating Diffusion of Innovation: A Case Based Approach to Explore and Build a Sustainable Framework Relevant For 21 Century - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Innovation and its successful diffusion into social system has been an area of prodigious interest among researchers and academicians across the world. Behavioural scientists and social researchers have been attempting to identify the process and stages through which adoption of an innovation takes place among the masses, and consequently, postulated number of theories illustrating the process of diffusion. Since the time Everett Rogers, one of the noteworthy contributors to the theory of diffusion, categorised people into five different segments with descending rate of adoption (Innovators, Early adopters, Early majority, Late majority and Laggards), there has been an accepted belief that all innovations follow these five stages of diffusion. The adoption of any new innovation is primarily triggered by a set of individuals highly innovative and sophisticated in nature. It is the demonstration effect exhibited by these individuals which makes the innovation acceptable st to the masses. However, the explosion of social media in 21 Century and its universal adoption has led to something called as ’Innovation optimism’, coined by Kit Yarrow in her book, “Decoding the New Consumer Mind”, who opines that more and more people across the world are transforming into innovative customers with tendency to take higher risk in the context of adopting new innovation. The concept of ’Lead market’ popularised by Marian Beise also considered customer sophistication to be the antecedent of innovation diffusion attributing most of the Global diffusion to developed Countries, until Rajnish Tiwari and Cornelius Herstatt argued that the developing Countries with low per capita income can also lead diffusion of innovation, where the sophistication of customer is offset by size of the population. Interestingly, the Brand Value Chain, developed by Kevin Lane Keller, also appears to have high degree of relevancy in this context, which provides a four stage framework to transform marketing investments into shareholders value. The present study is an attempt to explore the possibilities of accelerating the process of diffusion of innovation by adopting an integrated approach, combining and remodelling the Lead market theory and Keller’s Brand Value Chain through case study method. The framework may be instrumental in triggering, sustaining and accelerating mass adoption of socially beneficial innovation. The researchers intend to extract elements from lead market theory and incorporate as adoption multipliers or catalyzers in Keller’s Brand Value Chain expecting to smoothen the process of diffusion.